Removal of Nonmyrmecochorous Seeds by Ants: Role of Ants in Cattle Grasslands - Selene Escobar-Ramírez; Sebastián Duque; Natalia Henao; Alejandra Hurtado-Giraldo; Inge Armbrecht (Psyche: A Journal of Entomology)
Livestock production models prevailing in Colombian Andes are simplified treeless pastures for extensive ranching, with the consequent reduction of environmental services, such as seed dispersal, due to lack of primary dispersers, scarcity of adequate sites for seedling establishment and competition with grasses. This study evaluated if, in these harsh environments, ants can promote the colonization of arboreal species through directed dispersion of seeds towards the nests. Ten seeds of each species were offered to ants in six grazing pastures. Ants removed 25% of the seeds (1827) in 48 hours. Preference for arillated and small-to-medium sized seeds, such as Pithecellobium dulce, and Guazuma ulmifolia, was observed. Cyphomyrmex major, Ectatomma ruidum, Solenopsis geminata and Atta cephalotes were the key ant species in seed removal. It was concluded that functional ant groups present in the pastures could contribute to secondary dispersion of seeds with potential for restoration.